Clinical business intelligence to prevent stroke accidents - Gonçalves, Nuno (2016)
Stroke is considered the third main cause of death among all population, without distinguishing genders, led by heart diseases in first place. In other hand, despite representing a significant number of mortality, these diseases are the causes for a long-term disability in all countries with a vast recovery time going parallel with its costs. However, leaving aside this facts, stokes and heath diseases can also be easily prevented considering the outcome. This paper presents a new methodology to prevent these events to happen by using segmentation methods, which allows distinguishing and aggregating clusters of historical records, classification methods, such as Artificial Neural Networks, capable of classifying a new record according to its distribution among the clusters. A Multi-Agent Case Based Reasoning system is also proposed to evaluate solutions based in a similar case.